Modeling of particle size and energetic requirement in amaranth grain ball-milling - Diego Fernando Roa Acosta; Jesus Eduardo Bravo; Carlos Alberto Gonzalez (Revista U.D.C.A Actualidad & Divulgación Científica, 2019)
Amaranth flour is of high nutritional value, which makes it a potential food. Grinding of the grains is a necessary operation to obtain products with physical properties that provide the food products with adequate characteristics. To analyze the effect of grinding velocity and time on the particle diameters and physical properties of Amaranth flour by ball mill, a Doehlert design with triplicate at the central point was used. The tests were carried out with the mass ratio (balls/samples) (R1:5). Granulometry curve of each design system was fitted to the Rosin-Ramler-Bennet and Holmes-Hukki equations. A found a very significant effect of the velocity on the particle diameters (D50, D63 and D80). The flour obtained were modeled satisfactorily (r2>0.99) by using the Rosin-Ramler-Bennet equation, where the homogeneity index of (n1) was obtained, which was directly influenced by the milling energy. By using the Holmes-Hukki model, were able to model the characteristic diameters with the grinding energy; a critical region was observed between 100μm and 200μm, where lost efficiency in the size reduction. The excess energy, released in the critical region, caused the decrease in starch crystallinity and structural changes in the protein, which affect the functional properties of the flour. The planetary mill is emerging as an effective mean of modifying the functional properties in the development of new food products.